Interplay of hypoxia, immune dysregulation, and metabolic stress in pathophysiology of type 1 diabetes - Mittal, Rahul; Lemos, Joana R. N.; Chapagain, Prem; Hirani, Khemraj (Frontiers in Immunology, 2025)
Type 1 diabetes (T1D) is an autoimmune disease characterized by the progressive destruction of pancreatic β-cells, leading to insulin deficiency and chronic hyperglycemia. While immune-mediated mechanisms of β-cell destruction are well-recognized, emerging evidence highlights hypoxia as a silent yet critical contributor to T1D pathogenesis. Hypoxia in the pancreatic islets arises from inflammation, vascular dysfunction, hyperglycemia, and immune cell infiltration, creating a microenvironment that exacerbates β-cell dysfunction and amplifies autoimmune responses. Hypoxia-inducible factors (HIFs) play a dual role in regulating adaptive and maladaptive responses to hypoxia, influencing β-cell survival, immune activation, and oxidative stress. Specifically, hypoxia promotes the polarization of macrophages toward a pro-inflammatory M1 phenotype, enhances the differentiation of Th17 cells, and impairs the function of regulatory T cells (Tregs), thereby shifting the immune landscape toward sustained autoimmunity. This perspective discusses the multifaceted role of hypoxia in driving immune dysregulation and β-cell vulnerability in T1D as well as highlights the need for innovative research approaches to target this pathway. We propose future directions that emphasize the development of advanced experimental models to mimic the interplay between hypoxia, hyperglycemia, and immune responses in clinically relevant conditions. Furthermore, we highlight the potential of therapeutic strategies that target hypoxia and its downstream effects to preserve β-cell function and modulate autoimmunity. Collaborative efforts across disciplines will be crucial to translating these insights into clinical innovations that improve outcomes for individuals with T1D.